Food Sovereignty from A National Defense and Security Perspective - Elphis Rudy; Ivan Yulivan; THSB Hutabarat; Guntur Eko Saputro (Yayasan Sembilan Pemuda Indonesia, 2026)
Food sovereignty is a strategic pillar in maintaining national sustainability and supporting the stability of national defense and security. Dependence on food imports, unequal distribution, climate change, and global geopolitical dynamics have the potential to weaken national resilience if not managed comprehensively. This article aims to analyze the concept and role of food sovereignty from the perspective of Indonesia’s national defense and security, and to identify its strategic implications for strengthening national resilience. This research uses a literature review method by reviewing various scientific sources, including reputable national and international journals, academic books, government policy documents, and reports from related institutions relevant to food, defense, and national security issues. The results of the study indicate that food sovereignty functions not only as an instrument for meeting the basic needs of the community but also as a strategic non-military element in the national defense system. Strengthening food sovereignty contributes to social stability, controlling potential conflicts, increasing national resilience against non-traditional threats, and strengthening the country’s bargaining position in the global arena. Therefore, integrating food policy with national defense and security policy is an urgent strategic necessity. This article recommends the need for a cross-sectoral approach, strengthening the role of the state, and synergy between defense, security, and food development actors to support sustainable national resilience and sovereignty.